2019
DOI: 10.1038/s41598-019-39742-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in initiation and regulation of complement lectin pathway influence postoperative outcome after pediatric cardiac surgery involving cardiopulmonary bypass

Abstract: Congenital heart disease (CHD) often requires surgical intervention, and is sometimes associated with life-threatening post-operative complications. We have investigated some factors of the innate immune system involved in the initiation or regulation of complement lectin pathway activation (MASP-1, MASP-2 MASP-3, MAp19, MAp44, ficolin-3) and related them to complications and prognosis in 190 pediatric patients undergoing CHD repair with the use of cardiopulmonary bypass (CPB). Patients with MAp44 levels ≤1.81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
(60 reference statements)
1
4
0
2
Order By: Relevance
“…We noted that cardiac surgery with CPB has been shown to modulate leukocyte recruitment and transmigration ( Rossaint et al, 2012 ), much more than cardiac surgery without CBP ( Tomic et al, 2005 ). Specifically, our findings support a prominent role for ficolin-mediated activation of the lectin pathway of complement during cardiac surgery with CPB, likely in response to damage and pathogen-associated molecular patterns, and CPB circuitry ( Garred et al, 2009 , 2016 ; Michalski et al, 2019 ). In addition to regulating coagulation, ficolins augment inflammatory cytokine release and leukocyte chemotaxis.…”
Section: Discussionsupporting
confidence: 66%
“…We noted that cardiac surgery with CPB has been shown to modulate leukocyte recruitment and transmigration ( Rossaint et al, 2012 ), much more than cardiac surgery without CBP ( Tomic et al, 2005 ). Specifically, our findings support a prominent role for ficolin-mediated activation of the lectin pathway of complement during cardiac surgery with CPB, likely in response to damage and pathogen-associated molecular patterns, and CPB circuitry ( Garred et al, 2009 , 2016 ; Michalski et al, 2019 ). In addition to regulating coagulation, ficolins augment inflammatory cytokine release and leukocyte chemotaxis.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, they may prevent certain infections or development of some malignancies via direct lysis of cells expressing pathogen/danger-associated molecular patterns or by enhancement of phagocytosis [12][13][14][15] . On the other hand, complement-activating lectins may be involved in excessive or chronic inflammation which may be harmful to the host, leading in some cases to organ failure or carcinogenesis, respectively [16][17][18] .…”
mentioning
confidence: 99%
“…Larsen et al (2019) showed that low MASP-1 concentrations were associated with clotting disorders in patients with septic shock [ 34 ]. Michalski et al (2019) demonstrated that children undergoing surgical correction of congenital heart disease with low pre-operative MAp44 concentration were more likely to suffer from post-operative complications such as systemic inflammatory response syndrome (SIRS), renal failure, multiorgan dysfunction (MODS), or low cardiac output syndrome (LCOS), while high MASP-1 and low MASP-3 were often associated with fatal outcome [ 35 ].…”
Section: The Masp1/3 Gene and Its Products—maspmentioning
confidence: 99%